CLINICAL AND RADIOLOGICAL FEATURES OF PNEUMONIA IN YOUNG CHILDREN WITH ACUTE HERPETIC STOMATITIS - Aliev Ахмаджон; Abdullaev Дониёр (International Journal of Scientific Pediatrics, 2025)
Many problems of X-ray diagnostics of pneumonia in young children still remain unresolved and determine the need for their study. Purpose of the study. To study the clinical and radiological features of pneumonia in young children with acute herpetic stomatitis. Materials and methods. In this study, 60 children from the main group with acute herpetic stomatitis against the background of pneumonia are treated, for whom clinical and diagnostic characteristics are presented. The control group included 32 children with developed focal pneumonia. 23.5% of children with acute herpetic stomatitis were under 6 months, 53.1% - under 1 year and 33.4% - under 2 years. In the control group, 76.5% of children were under 1 year, and the remaining 23.5% were children over 1 year. Results. Acute pneumonia against the background of acute herpetic stomatitis is characterized by a severe course. These patients have pathological changes in the gastrointestinal tract and they aggravate the course of pneumonia. When analyzing the radiographic data of the lungs, a bilateral focal nature of the pneumonic process was observed. Conclusion. When analyzing the radiographic data of the lungs, most children had pneumonia against the background of acute herpetic stomatitis; the lungs had a bilateral focal nature of the pneumonic process.